2022
DOI: 10.1186/s12974-022-02575-y
|View full text |Cite
|
Sign up to set email alerts
|

Chronic allergic lung inflammation negatively influences neurobehavioral outcomes in mice

Abstract: Background Asthma is a major public health problem worldwide. Emerging data from epidemiological studies show that allergies and allergic diseases may be linked to anxiety, depression and cognitive decline. However, little is known about the effect of asthma, an allergic lung inflammation, on cognitive decline/behavioral changes. Therefore, we investigated the hypothesis that allergic lung inflammation causes inflammation in the brain and leads to neurobehavioral changes in mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…Chronic allergic lung inflammation or systemic inflammation due to chronic obstructive pulmonary disease (COPD) may adversely affect neurobehavior, and the evidence here supports the central nervous effects of peripheral inflammation ( Pelgrim et al, 2019 ; Kanaya et al, 2022 ). The current definition of the “lung-brain axis” focuses more on the complex regulatory relationship between the microbiome, the lungs, and the brain, i.e., the microbiome located in the lungs can influence the both organs and participate in the regulation of respiratory and neurological diseases, and conversely, respiratory and neurological diseases can lead to alterations in the structure and diversity of the lung microbiome ( Hosang et al, 2022 ).…”
Section: Prevention and Treatment Strategies Based On Peripheral Infl...supporting
confidence: 58%
“…Chronic allergic lung inflammation or systemic inflammation due to chronic obstructive pulmonary disease (COPD) may adversely affect neurobehavior, and the evidence here supports the central nervous effects of peripheral inflammation ( Pelgrim et al, 2019 ; Kanaya et al, 2022 ). The current definition of the “lung-brain axis” focuses more on the complex regulatory relationship between the microbiome, the lungs, and the brain, i.e., the microbiome located in the lungs can influence the both organs and participate in the regulation of respiratory and neurological diseases, and conversely, respiratory and neurological diseases can lead to alterations in the structure and diversity of the lung microbiome ( Hosang et al, 2022 ).…”
Section: Prevention and Treatment Strategies Based On Peripheral Infl...supporting
confidence: 58%
“…Although serum cytokines were not measured in this study, we and others have previously shown that young adult SHIP-1−/− mice on a C57BL/6 background exhibit increased circulating cytokines, such as IFNγ, TNFα, IL-4, IL-6, G-CSF, and GM-CSF [12,88]. This may alter the integrity of the blood-brain barrier and lead to increased cytokine levels in the brain [89,90], ultimately enhancing neuroimmune responses and obscuring the effect of the intrinsic loss of SHIP-1 activity in microglia. Therefore, future studies utilizing a combination of conditional knockout models and ex vivo cell culture experiments are needed to fully define the intrinsic role of SHIP-1 in microglia.…”
Section: Limitations and Future Directionsmentioning
confidence: 77%
“…(4) Whether the relationship between asthma and olfactory dysfunction is mediated or directly related by nasal diseases lacks relevant evidence. A summary of changes in brain network/activity, mediators, and related brain regions involved in the response of the brain in asthma is shown in Table 2 ( 12 , 21 , 31 , 34 , 37 , 42 , 44 , 49 , 53 , 56 , 58 , 59 , 68 , 70 , 72 , 74 , 78 , 82 , 97 , 113 , 114 ).…”
Section: Summary and Prospectmentioning
confidence: 99%
“…In addition to inflammatory factors, Kanaya et al found elevated levels of vascular endothelial growth factor (VEGF) in the blood of asthmatic mice and high concentrations of c-FOS protein, and glial fibrillary acidic protein (GFAP) deposition was detected in their brain regions, which is known to increase the permeability of the BBB. In addition, GFAP is a typical astrocyte injury marker, whereas c-FOS protein expression elevates when mast cells are activated in the brain, thereby indicating that inflammatory factors may infiltrate brain regions through the destruction of the BBB to activate neurons and mast cells in the brain, impair astrocyte function, disrupt mood regulation, and produce depressive disorders (82,83). Depression and anxiety disorders, as common internalization disorders, involve many overlapping regulatory mechanisms in the pathogenesis of asthma, such as the activation of brain regions by oxidative stress, damage to brain structure by inflammatory factors, and feedback regulation of the HPA axis.…”
Section: Asthma and Depressionmentioning
confidence: 99%
See 1 more Smart Citation